Discovery and characterisation of cysteine-rich peptides from Withania somnifera - Ng, Fang Lin (2017)
Known as Ashwagandha and Asgand respectively in the Ayurveda and Unani system of medicine, Withania somnifera is a plant whose leaves and roots possess many pharmacological properties such as tonic, anti-inflammatory, immunomodulatory, and aphrodisiac among others and, as a result, is used for thousands of years to treat illnesses ranging from general weakness, arthritis, to infertility. Cysteine-rich peptides (CRPs) are molecules containing disulfide bonds which account for its stability to thermal, chemical, and enzymatic degradation. It is produced by many organisms, mainly for defence. Due to its size and stability, CRPs are often utilised scaffolds in drug designing. In this study, we report the isolation and characterisation of a CRP, wS1, from W. somnifera. The CRP wS1 shows high homology with the recently reported lybatides, isolated from Lycium barbarum. Similar to other CRPs, wS1 display high stability towards thermal, acid and enzyme degradation. In addition, we also demonstrated the cell penetrating ability of wS1.